Effect of Gamified, Mobile, Cloud-Based Learning Management System (GMCLMS) on student engagement and achievement - Hosnia M. M. Ahmed; Hassan A. El-Sabagh; Doaa M. Elbourhamy (International Journal of Educational Technology in Higher Education)
Abstract Using mobile technologies and cloud computing with an approach of gamification stimulates and enriches the learning management system (LMS) for a unique creative learning environment that fosters boundless opportunities for learners. Today’s learners seek self-paced and motivating experiences. This study shows the importance of integrating attractive features within e-learning platforms to improve students’ achievement and engagement. This study aims to develop a Gamified Mobile Cloud-based Learning Management System (GMCLMS) and assess how it affects academic achievement and student engagement in the Object-Oriented Programming (OOP) course. Moreover, the study aims to outline and compare the proposed GMCLMS with conventional learning Management Systems (LMS). The study employs mixed research methods, using the development approach for GMCLMS and a quasi-experimental design for conducting the research. The findings reveal that the experimental group performed significantly better than the control group. Such results show that GMCLMS might be able to strategically involve students in their learning activities. The proposed system reinforcing the students’ engagement with a core OOP concepts instruction which was coupled with large effect sizes and a high Black gain ratio, underscores balanced student engagement development. These findings align with the broader literature on gamification in learning, confirming its potential to reinforce learning outcomes. This paper offers three practical suggestions: creating a foundation for the development and implementation of (GMCLMS), maximizing the impact of (GMCLMS), and enhancing the cost-effectiveness of education. The findings imply that integrating cloud-based and gamified systems in educational frameworks can improve student engagement as well as learning achievements, thus expanding the body of evidence for modern educational technologies. The findings offer actionable insights for educators and educational institutions from a factual rather than theoretical perspective.